2004
DOI: 10.1002/elps.200406024
|View full text |Cite
|
Sign up to set email alerts
|

Changes in mobile phase ion distribution when combining pressurized flow and electric field

Abstract: The distribution of ions in a capillary with both pressurized flow and an electric field has been studied. We have earlier reported that the overall concentration of ions increase in a capillary with high electric field and a pressurized flow. Now we describe how the ions are distributed in the capillary both along the capillary length and in the radial direction as a result of the parabolic flow profile. We have combined current measurements with finite element techniques in order to get better understanding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…The only parameter that significantly can increase t change is therefore the electric field strength E. Thus, a high electric field is desirable when a high effect on the separation is sought. The limitation of the magnitude of the electric field that can be applied over a capillary LC column is mainly set by the current through the column and the Joule heating that the current produces [173,174]. It has been noted that in a column with pressurized flow, the current became unex- pectedly high, which further restricts the EF-LC technique [173,174].…”
Section: Controlling the Retention With Electricitymentioning
confidence: 99%
See 1 more Smart Citation
“…The only parameter that significantly can increase t change is therefore the electric field strength E. Thus, a high electric field is desirable when a high effect on the separation is sought. The limitation of the magnitude of the electric field that can be applied over a capillary LC column is mainly set by the current through the column and the Joule heating that the current produces [173,174]. It has been noted that in a column with pressurized flow, the current became unex- pectedly high, which further restricts the EF-LC technique [173,174].…”
Section: Controlling the Retention With Electricitymentioning
confidence: 99%
“…The limitation of the magnitude of the electric field that can be applied over a capillary LC column is mainly set by the current through the column and the Joule heating that the current produces [173,174]. It has been noted that in a column with pressurized flow, the current became unex- pectedly high, which further restricts the EF-LC technique [173,174]. However, it seems to us that the application of electric fields in LC can be of interest for focusing analytes in the beginning of the column after the injection [137].…”
Section: Controlling the Retention With Electricitymentioning
confidence: 99%
“…Recent experiments have demonstrated that another strategy may be implemented with success when the analyte is charged [38][39][40][41][42][43][44][45][46]. This amounts to focusing a targeted analyte by opposing two means of transport within the separative microchannel: a constant one-direction solution flow of average velocity v avg which carries the analyte and a counter-direction electrokinetic force [47][48][49][50][51][52][53][54][55][56][57][58] (which depends on the analyte charge, q = z|e|, and its diffusion coefficient, D) whose intensity increases continuously along the microchannel separation length.…”
Section: Introductionmentioning
confidence: 99%